The influence of polypropylene laminated paper on the breakdown strength of insulation for high temperature superconducting cable - Dung, Nguyen Van; Khoa, Hoang Dang (Vietnam Journal of Science and Technology, 2020)
Polypropylene Laminated Paper (PPLP) and Kraft paper has been used as ac power insulation for conventional cable as well as high temperature superconducting (HTS) cable because of its prominent insulating characteristics. However, research on the use of PPLP/Kraft insulation for HTS cables are thinly scattered. In this paper, the effect of PPLP on the breakdown strength of PPLP/Kraft multi-layer sample impregnated with liquid nitrogen (LN2) under ac and impulse applied voltage was studied. In addition, the breakdown strength characteristics of PPLP and Kraft samples were also investigated in order to determine breakdown strength characteristics of PPLP/Kraft insulation directly. It was found from the experimental data that the breakdown strength increases as the component ratio of PPLP in the PPLP/Kraft sample increases and is slightly affected by the inserting position of PPLP but in impulse case, the breakdown strength strongly depends on the number of PPLP and the relative position of PPLP